Improved compliance of individual taxpayers through tax audit (Study at one of the Primary Service Offices in Bandung) - Hasanah, Ai; Najwa, Haritsatun; Nurpadhilah, Siti; Ramadhani, Gita Indah; Putriyani, Risna Amel; Sidharta, Iwan (Goodwood Publishing, 2023)
Purpose: This study aims to determine the increase in individual taxpayer compliance through tax audits. Research methodology: The researcher used a cross-sectional survey approach to determine the effect of tax audits on increasing individual taxpayer compliance, so the researchers surveyed tax examiners at one of the primary service offices in Bandung. The questionnaire was deployed in a structured manner and provided to 40 employees closely related to their duties as tax auditors. To test the effect of research variables, the researchers used simple regression analysis techniques to determine the magnitude of the effect of tax audits on individual taxpayer compliance. Results: The results of the study show that there is an effect of tax audits on taxpayer compliance. The results of the study indicate that the implementation of tax audits will be able to increase taxpayer compliance. Limitations: This study only examines the perception of employees who conduct tax audits. In addition, it only uses a small sample and only tests, individual taxpayers, so it cannot generalize the study results. Contribution: This study strengthens previous research and the theoretical basis of compliance in tax studies in Indonesia Novelty: This research complements research on taxpayer compliance that focuses on tax audits so that this research can add to the diversity of individual taxpayer compliance research.